Repetition Figures as a Cohesive Mechanism in Sava’s Life of Saint Simeon - Jekić, Sara R. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
At the heart of our research were figures of repetition as a cohesive mechanism in Sava’s Life of Saint Simeon. Based on representative examples, the method of working on the text, inductive and deductive reasoning, but also connecting the science of literature and linguistics of the text, we will try to show whether and to what extent the presence of repetition figures contributed to greater coherence of the text. Therefore, our analysis will not be reduced only to lower textual units, but also to higher ones, such as paragraphs, chapters, and the text as a whole, thus trying to penetrate the meaning of its entire organization. Considering that lexical and syntactic repetitions are the most important for textual analysis, i.e. figures that are created by repeating lexemes, phrases or sentences, they are primarily in the focus of research.